2021
DOI: 10.1002/adfm.202104254
|View full text |Cite
|
Sign up to set email alerts
|

A New Wide Bandgap Semiconductor: Carbyne Nanocrystals

Abstract: Deep ultraviolet (DUV) photodetectors (PDs) always and inevitably face a drastic working environment such as high temperature. However, DUV PDs based on the reported wide bandgap semiconductor materials cannot simultaneously possess high stability and high performance at high temperatures. Here, for the first time, a new wide bandgap semiconductor material, carbyne nanocrystals (CNCs), is reported. The constructed DUV PD made from CNCs demonstrates high‐performance and high stability at the temperature of 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The stable angular detection ability under high temperatures demonstrates that the PSD is significant potential for applications in severe working conditions such as those of astronomy, flame detection, and engine monitoring. [67,68]…”
Section: Resultsmentioning
confidence: 99%
“…The stable angular detection ability under high temperatures demonstrates that the PSD is significant potential for applications in severe working conditions such as those of astronomy, flame detection, and engine monitoring. [67,68]…”
Section: Resultsmentioning
confidence: 99%
“…The electronic structure of a solid can determine its basic properties, such as electrical properties, thermal properties, magnetic properties, and so on. In order to deeply explore the relationship between the internal electronic structures and energy bands of compounds 1 and 2 , we study their band structures. The band structures of compounds 1 and 2 were then investigated. When the conduction band minimum is at the same position as the valence band maximum, it is a direct band gap semiconductor; otherwise, it is an indirect band gap semiconductor. , As shown in Figure e,f, both compounds 1 and 2 are indirect band gap semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…9 Recently, Pan et al reported the first synthesis of carbyne nanocrystals by laser ablation in liquids (LAL). 10 Since then, a large number of studies on carbyne nanocrystals have emerged, [11][12][13] which implies that a new era of carbyne science and technology is coming. 8 Note that Babaev and Cuseva prepared a solid carbon film by pulsed plasma deposition of carbon clusters generated by a vacuum arc, and they called this solid film to be "linear-chained carbon (LCC)" because they believed that an energetic ion beam can destroy the sp 2 or sp 3 hybrid structures of carbon and make them into sp hybrids.…”
Section: Introductionmentioning
confidence: 99%